Dec 282017

Interesting display of various shapes with gravational intersection. | |||
---|---|---|---|

File Name | File Size | Zip Size | Zip Type |

GUTS.DOC | 1150 | 569 | deflated |

GUTS.EXE | 11552 | 6682 | deflated |

# Download File GUTS.ZIP Here

## Contents of the GUTS.DOC file

Program: Guts.exe (windows application)

Author : Wes Cherry (wesc) 3.1147

Release: Beta

EQUATIONS OF MOTION:

--------------------

Force & Acceleration:

---------------------

Uses a modified version of the uniform graviatitional formula:

(Inverse rather than inverse squared)

m * m m * m

F = G ----- rather than F = G -----

r r*r

This is done becuase the patterns are more interesting and it avoids having

to compute a square root when converting F to it's component vectors.

Derivation:

m2

|\

| \ Given:

^ | \ m1*m2

y | \ F = G -------

|___0\m1 r

x>

(0 = theta)

Fy = F Sin 0; Sin 0 = y/r

m1*m2 y

Fy = G ----- * -

r r

Ay = Fy / m1

So:

m1 * y

Ay = G --------

r * r

For x & z the equations are the same.

Since each body attracts each other, the acceleration is computed for each

body to all other bodies.

Velocity & Position:

--------------------

Since

dV/dt = A, dV = Adt

& dX/dt = V, dX = Vdt

Author : Wes Cherry (wesc) 3.1147

Release: Beta

EQUATIONS OF MOTION:

--------------------

Force & Acceleration:

---------------------

Uses a modified version of the uniform graviatitional formula:

(Inverse rather than inverse squared)

m * m m * m

F = G ----- rather than F = G -----

r r*r

This is done becuase the patterns are more interesting and it avoids having

to compute a square root when converting F to it's component vectors.

Derivation:

m2

|\

| \ Given:

^ | \ m1*m2

y | \ F = G -------

|___0\m1 r

x>

(0 = theta)

Fy = F Sin 0; Sin 0 = y/r

m1*m2 y

Fy = G ----- * -

r r

Ay = Fy / m1

So:

m1 * y

Ay = G --------

r * r

For x & z the equations are the same.

Since each body attracts each other, the acceleration is computed for each

body to all other bodies.

Velocity & Position:

--------------------

Since

dV/dt = A, dV = Adt

& dX/dt = V, dX = Vdt

December 28, 2017
Add comments